Key steps in unconventional secretion of fibroblast growth factor 2 reconstituted with purified components - Steringer, Julia P; Lange, Sascha; Čujová, Sabína; Šachl, Radek; Poojari, Chetan; Lolicato, Fabio; Beutel, Oliver; Müller, Hans-Michael; Unger, Sebastian; Coskun, Ünal; Honigmann, Alf; Vattulainen, Ilpo; et al. (eLife, 2017)
FGF2 is secreted from cells by an unconventional secretory pathway. This process is mediated by direct translocation across the plasma membrane. Here, we define the minimal molecular machinery required for FGF2 membrane translocation in a fully reconstituted inside-out vesicle system. FGF2 membrane translocation is thermodynamically driven by PI(4,5)P2-induced membrane insertion of FGF2 oligomers. The latter serve as dynamic translocation intermediates of FGF2 with a subunit number in the range of 8-12 FGF2 molecules. Vectorial translocation of FGF2 across the membrane is governed by sequential and mutually exclusive interactions with PI(4,5)P2 and heparan sulfates on opposing sides of the membrane. Based on atomistic molecular dynamics simulations, we propose a mechanism that drives PI(4,5)P2 dependent oligomerization of FGF2. Our combined findings establish a novel type of self-sustained protein translocation across membranes revealing the molecular basis of the unconventional secretory pathway of FGF2.
Keywords: Protein Multimerization; Membrane Transport Proteins; multimerizace proteinu; oligomerization; structural biology; Phosphatidylinositol 4,5-Diphosphate; fosfatidylinositol-4,5-difosfát; human; Molecular Dynamics Simulation; heparitinsulfát; Unconventional protein secretion; Secretory Vesicles; membránové transportní proteiny; Heparitin Sulfate; biochemistry; simulace molekulární dynamiky; fibroblastový růstový faktor 2; biophysics; phosphoinositide; protein translocation across membranes; reconstitution with purified components; sekreční vezikuly; Fibroblast Growth Factor 2